Socio-cultural Drivers of Psychosocial Distress and Resilience among Adolescent Girls in Nepal - Dhakal, Naba Raj; Thapa, Kavita (Cognition, 2026)
Psychological stress on adolescent girls in Nepal are shaped by socio-cultural factors such as gendered socialization, rapid changes in development and constricted access to mental health services. This study investigates how the nature of these challenges pose a threat to the girls’ mentality and identifies effective intervention ways for promoting their psychological, emotional and social improvement. Applying a mixed method approach, information has been collected form 32 adolescent girls aged 14-19 from two child care centers in Bhairahawa through counseling based observation, thematic discussion and In-depth Interview. The findings reveal that adolescent girls possess high level of emotional distress including anxiety, disturbances in sound sleeps and high family expectation of academic achievement. Moreover, patriarchal stereotypes, responsibilities for household works, digital media pressure — such as comparing body image with the videos shown such media and cyberbullying and cyberbullying—further complicates the psychological distress. Though remarkable challenges prevails, a few participants had a reach to professional counselling that highlights significant gaps in mental health facilities. However, structured group interventions such as the WHO’s Early Adolescent Skills for Emotions (EASE) program demonstrated positive outcome in enhancing emotional exposure, coping mechanism and garnering peer support.. The study concludes that socio-cultural contests rather than individual alone produce particular situation of psychological distress among girls. This sheds light on necessity of culturally fit intervention and gender-sensitive strategies in schools, families and communities to foster psychological and social aspects and strengthen resilience.